Penataan Rancangan Lokasi Instalasi Pengolahan Air Limbah Terpadu Kampus Institut Pertanian Bogor - Sigid Hariyadi; Niken Tunjung Murti Pratiwi; Majariana Krisanti; Adham Panji; Dwi Yuni Wulandari (Institut Pertanian Bogor, 2020)
Until now there has not been a centralized Wastewater Treatment Plant (WWTP) in IPB, even though there are wastewater treatments in several locations that are scattered in the campus area. Various activities on the Dramaga IPB campus have the potential to produce wastewater, such as laboratory activities, especially chemical and biological laboratories, canteens, offices, and dormitories. The existence of scattered laboratories requires a centralized and integrated WWTP. For this reason, mapping of wastewater distribution is needed to arrange the location of the wastewater treatment plant, within the campus. Interviews with the perpetrators of activities, measurement of wastewater quality, and sampling, were carried out at the work units producing wastewater on the campus of IPB. The distribution of wastewater was grouped according to the location of the work units producing waste and identified the types of waste produced (B3-dangerous and toxic and non-B3), then presented in a map. The map was used as a reference in determining the location of wastewater treatment plants. The results showed that each work unit contributes organic waste that was not too different, the source of inorganic and B3 wastewater distribution followed the location of the laboratory which was also quite scattered in the Dramaga IPB campus area. Based on the distribution of available waste, the presence of wastewater in the campus environment of IPB was divided into two regional groups. Therefore, the location of the wastewater treatment plant was directed at two locations, namely on the Northeast side (IPAL I) and the West side (IPAL II) of IPB campus. Keywords: wastewater characteristics, wastewater distribution, wastewater treatment plant